Morphological Variation of Sordellina punctata (Peters, 1880) with Notes on the Phylogenetic Position of the Genus within the Family Dipsadidae (Serpentes) - Miranda, Bruno Henrique V.; Fernandes, Daniel Silva (International Journal of Zoology, 2012)
Sordellina punctata (Peters, 1880) is a poorly known species from Brazil that, until recently, had an uncertain phylogenetic position. Sixty-one specimens of Sordellina punctata were examined, representing different localities encompassing the known geographic distribution of this taxon. Eight skulls and five hemipenes were prepared and described in detail and data on scale variation and color pattern as well as morphometric data were analyzed. The skull bones described, as well as the hemipenis of S. punctata, were compared to available data in the literature referred to members of the tribe Echinanterini and related taxa. Sordellina punctata presents an average snout-vent length of 31.5 cm for males and 40.2 for females and has an average of 149 ventral scales in males and 157 in females. The data presented here reinforce the necessity of a greater amount of osteological descriptive studies, especially of members of the tribe Echinanterini, in order to evaluate the recently proposed hypothesis of relationship of S. punctata and these taxa.